Serum Copper, Zinc, and Iron Levels in Patients with Alzheimer's Disease: A Meta-Analysis of Case-Control Studies - Li, Dan-Dan; Zhang, Wei; Wang, Zhan-You; Zhao, Pu (Frontiers in Aging Neuroscience, 2017)
ABSTRACT: Background: Many publications have investigated the association between metal ions and the risk of Alzheimer's disease (AD), but the results were ambiguous. Aims: The objective of this study was to assess the association between the serum levels of metals (copper/zinc/iron) and the risk of AD via meta-analysis of case-control studies. Methods: We screened literatures published after 1978 in the Pubmed, Embase, Cochrane library, Web of Science and ClinicalTrials.gov. Electronic databases. By using Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines, we performed a systematic review of the 407 publications, there are 44 of these publications met all inclusion criteria. The Review Manager 5.3 software was used to calculate available data from each study. Results: Consistent with the conclusions of other meta-analysis, our results demonstrated serum copper levels were significantly higher [MD = 9.27, 95% CI (5.02-13.52); p < 0.0001], and the serum zinc levels were significantly lower in AD patients than in healthy controls [MD = -6.12, 95% CI (-9.55,-2.69); p = 0.0005]. Serum iron levels were significantly lower in AD patients than in healthy controls after excluded two studies [MD = -13.01, 95% CI (-20.75,-5.27); p = 0.001]. Conclusion: The results of our meta-analysis provided rigorous statistical support for the association of the serum levels of metals and the risk of AD, suggesting a positive relationship between the serum copper levels and AD risk, and a negative relationship between the serum zinc/iron levels and AD risk.